2016
DOI: 10.1007/s11011-016-9920-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortical damage in Wernicke’s encephalopathy with good prognosis: a report of two cases and literature review

Abstract: Wernicke's encephalopathy (WE) is a thiamine deficiency-related condition, in which lesions are usually present in the periventricular and subcortical areas of the brain. However, lesions have also been found in atypical areas, such as the cerebral cortex. The present study summarizes the clinical outcomes and radiological features of WE with cortical impairment. We report two cases of cortical involvement in patients with WE, and review 22 similar cases from other reports. Among all 24 cases, 4 patients had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Cases with pathological findings in the bilateral cortex may lead to a poor outcome. [9] The MR imaging of our case showed hyperintense lesions in the bilateral medial thalami. The classical triad of Wernicke encephalopathy includes ophthalmoplegia, gait ataxia, and altered mental status.…”
Section: Discussionmentioning
confidence: 68%
“…Cases with pathological findings in the bilateral cortex may lead to a poor outcome. [9] The MR imaging of our case showed hyperintense lesions in the bilateral medial thalami. The classical triad of Wernicke encephalopathy includes ophthalmoplegia, gait ataxia, and altered mental status.…”
Section: Discussionmentioning
confidence: 68%
“…No exact frequency of seizure was found in the English literature among those with WE. Another retrospective study found that the frontal and parietal lobes, especially around the central sulcus, are the most susceptible areas [ 2 ]. Cortical involvement is usually seen as a sign of irreversible damage and poor prognosis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent irreversible brain damage due to untreated Wernicke's encephalopathy, thiamin replacement therapy administered along with dextrose fluid or parenteral nutrition solutions should be considered as prophylactic treatment in hospitalized cancer patients where enteral nutrition cannot be provided for an extended period. Batori et al [5] 1995 1 Gastric cancer Subtotal gastrectomy Arai et al [6] 1997 2 Gastric cancer Total gastrectomy Shimomura et al [7] 1998 3 Gastric cancer Total gastrectomy, subtotal gastrectomy Attard et al [8] 2006 1 Benign gastric tumor** Subtotal gastrectomy Karayiannakis et al [9] 2011 1 Pancreatic cancer Pancreaticoduodenectomy Rufa et al [10] 2011 10 Pancreatic cancer, colon cancer, gallbladder cancer, gallbladder adenoma Abdominal-perineal resection, gastro-entero-anastomosis, hemicolectomy, pancreaticoduodenectomy, cholecystectomy Busani et al [11] 2014 1 Duodenal cancer Pancreaticoduodenectomy Kilinc et al [12] 2015 1* Pancreatic cancer Pancreaticoduodenectomy Wu et al [13] 2016 1* Pancreatic cancer Pancreaticoduodenectomy Restivo et al [14] 2016 19 Gastric cancer, colorectal cancer Total/distal gastrectomy, hemicolectomy, anterior resection, abdominal perineal resection Tozzo et al [15] 2017 1 Gastric cancer Subtotal gastrectomy Tsao et al [16] 2017 1* Gastric cancer Subtotal gastrectomy AbdelRazek et al [17] 2018 1 Pancreatic cancer Pancreaticoduodenectomy Kim et al [18] 2019 1 Ampulla of vater cancer Pancreaticoduodenectomy Fedeli et al [19] 2020 2 Gastric cancer, colorectal cancer Subtotal gastrectomy, anterior resection of rectum Li et al [20] 2021…”
Section: Discussionmentioning
confidence: 99%
“…The primary malignancies documented in these studies were colorectal, gastric, pancreatic, and gallbladder cancer, pelvic sarcoma, acute myelogenous leukemia, inflammatory breast carcinoma, and multiple myeloma. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] To the best of our knowledge the present case is the first to report a Wernicke's encephalopathy in a patient diagnosed with cholangiocellular carcinoma. Previous case reports of Wernicke's encephalopathy in cancer patients after gastrointestinal surgery are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%